Changes in intrinsic functional brain connectivity related to occupational stress of firefighters. (August 2022) - Lee, Deokjong; Kim, Woojin; Lee, Jung Eun; Lee, Junghan; Kim, Yun Tae; Lee, Seung Koo; Oh, Sung Soo; Park, Ki Soo; Koh, Sang Baek; Kim, Changsoo; Jung, Young-Chul
Highlights: Brain FC related to occupational stress in firefighters was investigated. Job stress was negatively correlated with FC between the CEN and other networks. Job stress was negatively correlated with FC within the DMN. Job stress was positively correlated with FC between the SN and the DMN. Abstract: Firefighters are exposed to physical and mental threats in the working environment that put them at risk for occupational stress and burnout. Stress responses can impact the functional interactions between brain regions involved in emotional and cognitive regulation. The objective of this study was to investigate brain functional connectivity (FC) related to occupational stress in firefighters. Male firefighters ( n  = 77) completed the Korean Occupational Stress Scale questionnaire on occupational stress and underwent brain magnetic resonance imaging. Seed-based FC analyses were conducted by setting core regions of the large-scale functional networks as seeds. Subsequent correlational analyses detected relationships between occupational stress scale scores and brain FC. The results showed that occupational stress was negatively correlated with FC between the central executive network (CEN)-related brain regions and seed regions of other networks. Additionally, occupational stress was negatively correlated with FC within the default mode network (DMN), but positively correlated with FC between the salience network (SN) and the DMN. Changes in FC in large-scale neural networks are likely involved in occupational stress responses. Taken together, these results suggest that proper management of occupational stress may help prevent the occurrence of clinical problems caused by changes in brain functional networks.